Current-voltage and capacitance-voltage studies of nanocrystalline CdSe/Au Schottky junction interface - Sarangi S.N.; Adhikari P.K.; Pandey D.; Sahu S.N. (My University, 2025)
CdSe nanocrystalline thin films have been synthesized on indium tin oxide (ITO) substrates by an electrodeposition technique. A Schottky junction device in the configuration, ITO/nano-CdSe/Au has been fabricated to study the device interface properties by current (I)-voltage (V) and capacitance (C)-voltage (V) measurements and compared with the ITO/bulk-CdSe/Au device. The I-V characteristics of the nano-CdSe device shows a series resistance effect and C-V characteristics show the presence of surface/interface traps induced by a thin native oxide layer at the nano-CdSe/Au interface and is responsible to the deviation in the ideal Mott-Schottky behavior. The presence of a thin oxide layer on the CdSe nanocrystal surface has been identified from Rutherford backscattering (RBS) spectrometry. The low frequency capacitance response of the nano-CdSe device characteristics are being compared with the bulk device, which confirms the presence of surface/interface states within the band gap of CdSe nanocrystals. Mott-Schottky plots at different frequencies indicate the formation of a Schottky barrier between nano-CdSe and Au junction. © 2009 Springer Science+Business Media B.V.